(untitled) (Estudos em Design, 2021)
Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 29, n. 2 (2021) Adriana Gralow Alexandre Farbiarz Álvaro José Barbosa Sousa Ana Veronica Pazmino André Ribeiro de Oliveira Andréa Silva Angélica Adverse Antônio Ferreira Colchete Filho Beany Monteiro Cássia Letícia Carrara Clice Mazzilli Claudio Silva Cristina Portugal Cyntia Santos Malaguti Daniel Portugal Daniel Raposo Daniela Alves Deborah Christo Doris Kosminsky Edson Rufino de Souza Eloiza Andrade Corrêa Elizabeth Romani Everton da Silva Fernando Fogliano Frederico Braida Gabriel Patrocínio Gisela de Campos Haroldo Gallo Helena Bastos Helena Neumann Jade Piaia Jamille Noretza de Lima Lanutti Ione Maria Ghislene Bentz Joao Eduardo chagas Sobral José Carlos da Silva Juliana Bueno Kando Fukushima Kátia Carvalhaes Pêgo Katia Miller Leticia Affini Letícia Pedruzzi Fonseca Linda Linn Luiz Agner Márcio Guimarães Marcos Braga Maria Cristina Ibarra Mariana Cantisani Padu Mariano Lopes de Andrade Neto Maristela Mitsuko Ono Nelson Kuwahara Otniel Josafat López Altamirano Paula Ladin Rafaella Peres Ranielder Fábio de Freitas Raquel Noronha Ravi Passos Renata Cadena Ricardo Cunha Lima Rogério José Câmara Romero Tori Sandra Souza Sérgio Luciano da Silva Tiago Barros Pontes Silva Vera Damazio Verônica Freire Virginia Kistmann Viviane Nunes Wagner Bandeira Walter Neto